Analyzing library collection use with Excel - Greiner, Tony (American Library Association, 2007)
In this unique guide, two collection development experts show how to use Excel® to translate circulation and collection data into meaningful reports for making collection management decisions. Step-by-step instructions accompanied by screen shots allow anyone to use Excel® to quickly "crunch the numbers" that often bog down library use studies.